|x-1|> |x+1| maka penyelesaiannya adalah

Jawaban: 2

Jawaban

  • Jawaban diposting oleh: fiyan92

    1. (F o G) = \frac{x+5}{2x + 10 -3} = \frac{x + 5}{2x + 7}

       (F o G)^-1 = \frac{x + 5}{2x + 7} = y

       (F o G)^-1 = 2xy + 7y = x + 5

       (F o G)^-1 = 7y - 5 = x - 2xy (dikali -1)

       (F o G)^-1 = -7y + 5 = 2xy - x (y menjadi x dan x menjadi 1)

       (F o G)^-1 = \frac{-7x + 5}{2x - 1}(E.)

    2.

    (F o G) = \frac{3x + 4 + 1}{3x + 4 - 5} =

    (F o G)^-1 = \frac{3x + 5}{3x -1} = y

    (F o G)^-1 = 3x + 5 = 3xy -y

    (F o G)^-1 = y + 5 = 3xy -3x

    (F o G)^-1 = \frac{x + 5}{3x - 3}

    3.

    (G o F) = \frac{1}{3(2x + 5 - 7)} = \frac{1}{3(2x - 2)}

    (G o F)^-1 = \frac{1}{3(2x-2)} = y

    (G o F)^-1 = 3y = 2x - 2

    (G o F)^-1 = -2x = -3y -2

    (G o F)^-1 = 2y = 3y + 2

    (G o F)^-1 = 3x + 2 / 2

    (G o F)^-1 (4) = 3(4) + 2 / 2

    (G o F)^-1 (4)= 7 (A.)

    4.

    (f o g o h) = 3 - 2(3x +5) +2

    (f o g o h) = 3 -6x -10 + 2

    (f o g o h) = -6x -5

    (f o g o h)^-1 = -6x -5 = y

    (f o g o h)^-1 = -y -5 = 6x

    (f o g o h)^-1 = -x -6 / 5

    (f o g o h)^-1 (a) = -a -6 / 5 = -2

    -a -6 = -10

    -a = -4

    a = 4 (E.)

    5.

    f^-1 = \frac{x+3}{x-5} = y

    f^-1 = x + 3 = xy - 5y

    f^-1 = 5y + 3 = xy - x

    f^-1 = \frac{5x + 3}{x - 1} (C.)

Tahukah Anda jawaban yang benar?
|x-1|> |x+1| maka penyelesaiannya adalah...